2019
DOI: 10.1002/jbm.b.34423
|View full text |Cite
|
Sign up to set email alerts
|

In vitro toxicity assessment of hydrogel patches obtained by cation‐induced cross‐linking of rod‐like cellulose nanocrystals

Abstract: With the purpose of designing active patches for photodynamic therapy of melanoma, transparent and soft hydrogel membranes (HMs) have been fabricated by cation‐induced gelation of rod‐like cellulose nanocrystals (CNCs) bearing negatively charged carboxylic groups. Na+, Ca2+, Mg2+ have been used as cross‐linkers of cellulose nanocrystal (CNC). The biosafety of this material and of its precursors has been evaluated in vitro in cell cultures. Morphological changes, cell organelles integrity, and cell survival wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 40 publications
2
10
0
Order By: Relevance
“…This confirms without a doubt that the three CNCs/FA-CS-FITC nanosystems are non-cytotoxic to the MDA-MB-231 cells at concentrations below 200 µg mL −1 , with an in vitro cell viability quite above the 70% threshold [57]. These results are similar to those reported for other CNCs-based nanosystems with other tumor cell lines, such as the human breast adenocarcinoma MCF-7 cell line [58], and the A375 and M14 cells (malignant melanoma cell lines) [59].…”
Section: Cellular Viabilitysupporting
confidence: 78%
“…This confirms without a doubt that the three CNCs/FA-CS-FITC nanosystems are non-cytotoxic to the MDA-MB-231 cells at concentrations below 200 µg mL −1 , with an in vitro cell viability quite above the 70% threshold [57]. These results are similar to those reported for other CNCs-based nanosystems with other tumor cell lines, such as the human breast adenocarcinoma MCF-7 cell line [58], and the A375 and M14 cells (malignant melanoma cell lines) [59].…”
Section: Cellular Viabilitysupporting
confidence: 78%
“…, Mg 2? as gelling cations was developed to use in active patches for photodynamic therapy of melanoma (Meschini et al 2019). The cytotoxicity evaluation (MTT, morphological changes, organelles integrity) using two cell lines of melanoma and one cell line of human primary dermal fibroblasts exposed to the CNC membrane by direct and indirect contact tests demonstrated this hydrogel biocompatibility.…”
Section: Cytotoxicitymentioning
confidence: 99%
“…The percentage of cells spread was higher for Fe 3+ crosslinked gels compared to the Ca 2+ gels (except for the Ca 2+ gel with covalently attached PF), possibly due to the increased hydrophobicity and greater adsorption of serum proteins. However, this behavior can also be attributed to the certain toxicity of calcium ions, proven in a recent study by Meschini et al [ 118 ], where Ca 2+ was used as a gelling agent of negatively charged cellulose nanocrystals along with natrium and magnesium ions. However, as mentioned in the study, this high toxicity can be avoided if the excess of calcium cations from hydrogels are removed by appropriate rinsing or soaking treatments, and more attention is paid to the manufacturing process.…”
Section: Nanocellulose-based Materials In Pharmaceutical/medical Applicationsmentioning
confidence: 99%
“…Considering the toxicity evaluation performed on various CNC materials (wood and non-wood), it was observed that most of the studies indicate low or even negligible cytotoxic effects [ 118 , 133 , 138 , 161 , 179 ]. However, there are also some studies in literature that record a cytotoxic effect of CNC [ 179 , 180 , 183 , 195 ].…”
Section: Toxicological Evaluation and Potential Limitations Of Ncs-based Materialsmentioning
confidence: 99%